Papel de glicose e insulina no crescimento tumoral em modelo Balb/C-4T1 de adenocarcinoma mamário murino - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2020)
BACKGROUND: Once the majority of human breast cancers have shown overexpression of insulin receptors, glycose levels and insulin intake may possibly affect the breast cancer outcomes. However, the exact role high-fat diet, hyperglycemia and hyperinsulinemia in breast cancer outcome remains unclear. Thus, the aim of present study was to evaluate the role of high-fat diet, glycemia and insulin intake on murine breast adenocarcinoma tumor growth in vivo. METHODS: Adult female mice (Rodentia muridae, Mus musculus, Balb-C lineage) were submitted to subcutaneous implantation of murine breast adenocarcinoma cells, divided in four groups. Group 1 received only tumor implantation (4T1 cells), Group 2, tumor implantation and high-fat diet (4T1-HFD), Group 3, tumor implantation and insulin (4T1-INS) and Group 4 tumor implantation and high-fat diet (4T1-HFD-INS). Measurements and laboratory tests were taken at days 15 and 30 of experimentation. RESULTS: This paper presents macroscopic findings and laboratory tests. High fat diet is correlated to bigger tumor volume (p=0.0492), except if associated to insulin (0.0168), but not to higher glucose serum levels. Groups that received insulin showed smaller tumor growth amplitude, but there was no difference in glucose serum levels between any group at D30. Serum glucose levels were not correlated with higher tumoral volumes. Tumor invasion of upper left limb was incident in all groups (66.7% to 100%), with no difference between groups (p=0.9471). Pulmonary metastases were more frequent in groups that received insulin (p<0.05) or HFD plus insulin (p<0.05) when compared to group 1 (4T1).
Keywords: Neoplasia Mamária Experimental; Transtornos do Metabolismo de Glucose; Insulina; Dieta Hiperlipídica; Experimental Breast neoplasm; Glucose Metabolism Disorders; Insulin; Diet, High-Fat; CNPQ::CIENCIAS DA SAUDE::FARMACIA